Case report: Successful treatment of hyperbaric oxygen for radiation-induced hemorrhagic cystitis in a 95-year-old patient with bladder cancer - Lin, Li; He, Man; Zeng, Yanyan; Ni, Xiaoxiao; Guo, Yequn; Xie, Xiaojuan; Sun, Lingling; Huang, Huai (Frontiers in Oncology, 2025)
BackgroundSevere radiation-induced hemorrhagic cystitis (RHC) may ultimately require radical cystectomy. High-quality clinical evidence exists regarding the impact of hyperbaric oxygen therapy (HBOT) on RHC. However, there is a lack of reported data addressing the applicability of HBOT in very elderly patients (over 90 years old) with severe bleeding necessitating multiple blood transfusions.Case presentationThe patient is a 95-year-old male who suffered from severe hematuria due to RHC after 33 sessions of radiotherapy for muscle-invasive bladder cancer (T2N0M0, stage: II). After a series of subsequent therapies that failed to control the hematuria, the patient received 196 HBOTs between 11 October 2022 and 23 October 2023. Following a progressively adjusted HBOT protocol, the patient’s hematuria (urine red blood cell (RBC) count showed 210,859 RBC/μL at maximum) was effectively controlled, and his symptoms subsequently resolved after 69 HBOTs. After the 196th HBOT, pelvic MRI revealed a reduction in the size of the lesion on the left posterior wall of the bladder compared to prior assessments. This reduction was suggestive of diminished intravesical hematoma. As of 26 October 2023, it is noteworthy that the patient’s hemoglobin level has restored to the pre-hematuria level (106 g/L) with no need for blood transfusions for 8 consecutive months. Moreover, there was no recurrence of hematuria during the follow-up period. To the best of our knowledge, this report represents the first documented case of hematuria resolution in a patient over 90 years old with severe RHC.ConclusionThis case represents the first documented instance of successful hematuria resolution in a patient over 90 years of age with severe RHC. The positive therapeutic outcome achieved with personal protocol (1.4-1.6 ATA) in this 95-year-old patient, expands hyperbaric oxygen pressure options for elderly patients. Moreover, it also records a comprehensive dataset, including the time of the patient’s recurrence of hematuria and the subsequent trend of hematuria control, which contributes valuable evidence to the research on HBOT for the repair of bladder mucosal tissue.